Animal Welfare: A Livestock Challenge: un reto en la producción pecuaria - Muñoz, Rafael (Spei Domus, 2014)
Animal welfare has been a matter of concern through the past decades. Researches have proved it to be related to physical and psychological health of animals, and to production, reproduction and quality of livestock products. In this display that has caused some policies, standards and models, etc. to be created, the interest to provide good conditions for animals has been mainly based on economic and human use grounds. Based on this point of view, this article describes some important aspects to cause a critical position in the reader to encourage future discussion, which are less anthropocentric, about the primary production of livestock products.